Perception of health professionals on the prone position as a therapeutic strategy for patients with COVID-19 - Natiele Camponogara Righi; Rodrigo Della Méa Plentz; Pâmela Thaise Rosa De Marchi; Kaciane Roberta Brambatti; Andrieli Barbieri Garlet; Jean Mesquita; Andrea Passuelo de Oliveira; Jociane Schardong (Universidade de São Paulo, 2022)
ABSTRACT The COVID-19 pandemic has led to a great number of hospitalizations. A considerable number of cases progress to the severe form of the infection and death. Prone positioning is a therapeutic strategy with strong evidence of reduced mortality in patients with acute respiratory distress syndrome (ARDS). This study aims to assess if the prone positioning strategy is used by health professionals in hospitals to treat patients with COVID-19 on invasive mechanical ventilation and the professionals' perception of its effect on the mortality rate. This is a cross-sectional study, with a convenience sample composed of health professionals of both sexes working in hospitals throughout Brazil. Participants answered an online questionnaire composed of 16 questions using Google Forms, from July 2020 to September 2020. A total of 455 questionnaires were answered. Prone positioning is routinely performed in hospitals where 386 (95%) of the responding professionals work. Among them, 374 (96.9%) consider that the prone position strategy reduces hypoxemia and 289 (74.9%) consider that it reduces mortality in patients with COVID-19 and ARDS on invasive mechanical ventilation. Finally, most health professionals working in Brazilian hospitals perform and believe that prone positioning reduces hypoxemia and mortality in patients with COVID-19 on invasive mechanical ventilation.